'Every group carries the flavour of the admins': leadership on Flickr. (14th July 2011) - Holmes, Paul; Cox, Andrew M.
Although leadership in many types of online community has been recognised as important, relatively little has been written about its nature in informal communities, particularly in the context of Web 2.0. This study explores the role played by admins on the photo sharing site Flickr. Semi-structured interviews with six admins investigated roles and motivation in some depth. A content analysis was conducted to explore the character of admins' activities on discussion boards in four types of group. The interviews revealed the dedication that admins gave to the role. They saw their activities as one of the main critical success factors for any group. Groups were heavily shaped by admins. The content analysis revealed that admins play a wide range of roles in groups, with markedly varying emphasis between different group types.